2020
DOI: 10.1016/j.jas.2019.105057
|View full text |Cite
|
Sign up to set email alerts
|

The introduction of celadon production in North China: Technological characteristics and diversity of the earliest wares

Abstract: Celadon, technically a stoneware with a lime-rich glaze, had been produced in South China for more than two millennia before it was first made in the North in the second half of the sixth century. It appears to have been an immediate precursor to white porcelain, which was first produced by northern kilns. The compositions and microstructures of early northern celadons from kilns, residential sites and tombs in Shandong, Hebei and Henan provinces, and dated 550s-618 CE, have been determined by SEM-EDS. The maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Titanium and iron oxide are both present, with contents in the range of 0.54–0.79 wt% and 1.55–2.13 wt%, respectively. The glazes have a high level of calcium oxide (10–15 wt%), and the total quantity of K 2 O and Na 2 O in the glazes is generally between 2 wt% and 7 wt%, which is consistent with previous research on the early Xing wares (Huang et al, 2020; Ma, Ma, et al, 2018; Ma, Zhao, et al, 2021). The contents of Fe 2 O 3 and TiO 2 are in the range of 1.01–2.41 wt% and 0.13–0.50 wt%, respectively, causing variances in the glaze hues of the samples among white, green, and yellow.…”
Section: Resultssupporting
confidence: 88%
“…Titanium and iron oxide are both present, with contents in the range of 0.54–0.79 wt% and 1.55–2.13 wt%, respectively. The glazes have a high level of calcium oxide (10–15 wt%), and the total quantity of K 2 O and Na 2 O in the glazes is generally between 2 wt% and 7 wt%, which is consistent with previous research on the early Xing wares (Huang et al, 2020; Ma, Ma, et al, 2018; Ma, Zhao, et al, 2021). The contents of Fe 2 O 3 and TiO 2 are in the range of 1.01–2.41 wt% and 0.13–0.50 wt%, respectively, causing variances in the glaze hues of the samples among white, green, and yellow.…”
Section: Resultssupporting
confidence: 88%
“…Green glazed stoneware was the first high-fired ceramic made in North China and the technological precursor of early northern porcelain. It has been suggested that the northern green stoneware glaze was created following the original southern recipe: wood ash plus body material (Huang et al 2020). The Sr isotopic compositions of our Gongyi green stoneware glaze samples are very consistent at 0.715-0.718 for 87 Sr/ 86 Sr and 300-350 ppm for Sr concentration (Figure 1).…”
Section: The Chemical and Sr Isotopic Compositions Of Gongyi Northern...mentioning
confidence: 71%
“…The results of Sr isotope and chemical analysis of our early porcelain samples from Xing kilns show that body material was not the sole siliceous material in the glaze formula. Although green stoneware glaze from Xing kilns is not studied in this work, from its chemical composition reported in Huang et al (2020), we can see that it has a very similar chemical composition to Xing early porcelain, and there is also a Na 2 O content discrepancy between Xing green stoneware body and glaze which suggests that another raw material, apart from body material and wood ash, was included in the glaze recipe.…”
Section: The Siliceous Raw Materials Used For Glazes In Xing Kiln Pro...mentioning
confidence: 78%
See 2 more Smart Citations